2016
DOI: 10.6018/analesps.32.3.261641
|View full text |Cite
|
Sign up to set email alerts
|

El poder de los extravertidos: Evaluando la regulación de estados de ánimo positivos y negativos

Abstract: Título: El poder de los extravertidos: Evaluando la regulación de estados de ánimo positivos y negativos. Resumen: La extraversión es un rasgo de personalidad que ha sido sistemáticamente relacionado con el afecto positivo y el bienestar. Uno de los mecanismos que puede dar cuenta de estos efectos positivos es la habilidad para responder a los estados de ánimo tanto negativos como positivos. La investigación previa ha encontrado que el mayor mantenimiento de estados de ánimo positivos que logran los extraverti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In relation to the sixth hypothesis, results demonstrated differential correlates between different uses of internet and different components of well-being. Multivariate results confirmed that direct social interaction predicted life satisfaction (Hervás & López-Gómez, 2016;Lischetzke & Eid, 2006;Lucas, Dyrenforth, & Diener, 2008). Absence of predictive value for direct social contact on anxiety was expected because positive events and social support are less related to negative affect (Maybery et al, 2006).…”
Section: Discussionmentioning
confidence: 58%
“…In relation to the sixth hypothesis, results demonstrated differential correlates between different uses of internet and different components of well-being. Multivariate results confirmed that direct social interaction predicted life satisfaction (Hervás & López-Gómez, 2016;Lischetzke & Eid, 2006;Lucas, Dyrenforth, & Diener, 2008). Absence of predictive value for direct social contact on anxiety was expected because positive events and social support are less related to negative affect (Maybery et al, 2006).…”
Section: Discussionmentioning
confidence: 58%
“…), was also the focus of a series of articles (see Luciano, Leisser, Wright, & Martin, 2004;Luciano, Wright, & Bates, 2008;Roberts, 2002;Robinson, 2008). Indicative of how the ambivert has become a particularly Eysenckian concept, associated with his theories and methods of the biology of personality, the ambivert still occasionally appears in event-related potential (ERP; research that analyzes EEG [electroencephalography] data) experiments on personality outside of Personality and Individual Differences (e.g., Cai, Lou, Long, & Yuan, 2016;Georgiev, Christov, & Philipova, 2014;Hervas & Lopez-Gomez, 2016). The ambivert has also found its way outside of the Eysenckian lexicon and into more mainstream psychology and consequently, once again, into popular culture.…”
Section: The Ambivert At the Crossroads Of Type And Traitmentioning
confidence: 99%
“…Constituted and manifested as subjective states or dispositions towards environmental situations, several studies (Burce & Ian, 2012;Clark et al, 1994;Hervás & López-Gómez, 2016;Morán et al, 2017) confirm that PAs tend to be associated with extraversion and ANs with neuroticism (Aritio-Solana et al, 2022). However, it was the necessity to offer an evaluative instrument about them that led Watson et al (1988) to construct the Positive and Negative Affect Schedule questionnaire (PANAS), isolating 10 items alluding to PA and another 10 about AN, obtaining a score in terms of positive and negative affectivity, respectively.…”
mentioning
confidence: 99%